Implementasi Kurikulum 2013 dalam Pembelajaran Geografi sebagai Bagian Salah Satu Dasar Pembentukan Karakter Bangsa - Suhadi Rahman; Syafri Anwar; Khairani Khairani (Departement of Mathematics Education, 2022)
Education is a conscious and planned effort to make improvements and changes in the behavior, experience, and knowledge of students. Through education, it is hoped that a significant increase in the quality of human resources is expected. National education is a planned effort to build the culture and character of the Indonesian nation. Likewise with geography education. So, geography education is a science to support life throughout life and encourage the improvement of life. Therefore, geography learning is directed at developing the character of students to love their homeland